Effect of waste marble powder and rice husk ash on the microstructural, physico-mechanical and transport properties of foam concretes exposed to high temperatures and freeze–thaw cycles - Sutcu, Mucahit; Bayraktar, Oguzhan Yavuz; Benli, Ahmet; Elabade, Wiam Abdelmagid Taher; Gencel, Osman; Kaplan, Gökhan (Elsevier BV, 2021)
Abstract An experimental program was performed to evaluate the impact of rice husk ash (RHA) as cement replacement and waste marble powder (WMP) as sand replacement on the microstructural, mechanical and transport properties of foamed concrete exposed to high temperature and freeze–thaw cycles. For this, Portland Cement (PC) was replaced by RHA at 10% and 20%wt of binder and silica sand was replaced by WMP at 25% and 50%wt of fine aggregates to cast foamed concrete mixtures. Two different foam contents of 40 kg/m3 and 80 kg/m3 were used in the production of foamed concretes with water/binder (w/b) ratio of 0.70. Two reference mixtures were produced from silica sand and without RHA at each foam content. Other foam concretes were fabricated from 25% and 50% WMP instead of silica sand and 10% and 20% RHA instead of cement. Fresh properties of mixtures were evaluated by performing slump test. Transport properties of foam concretes were investigated, including porosity, sorptivity and water absorption after 90 days curing. Mechanical properties of foam concretes were investigated, including compressive and flexural strength ultrasonic pulse velocity (UPV) after 7, 28 and 90 days. Drying shrinkage and thermal conductivity of concretes were also studied after 90 days. Durability of concretes were also investigated after exposure to the temperature of 200, 400, 600 and 800 °C and freeze–thaw (F-T) cycles of 100 and 200 in addition to microstructure investigations. Results show that 10% RHA as cement substitute and 50% WMP as sand substitute give optimum percentage especially at late-age of 90 days at foam content of 40 kg/m3. The lowest drying shrinkage and sorptivity were obtained by using 10%RHA and 25%WMP. The results also indicate that water cooled specimens showed more strength loss than air cooled specimens after 200 °C. The worst F-T performance was obtained for the mixture containing 10% RHA and without WMP by 43.8 and 59.8% strength reductions.
Keywords: Physico-Mechanical Properties; Rice Husk Ash; Foam Concrete; High Temperatures; General Materials Science; Freeze-Thaw Cycles; Waste Marble Powder; 6. Clean water